2017
DOI: 10.18203/2394-6040.ijcmph20170050
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of cataract surgical coverage in India: findings from a population-based study

Abstract: Background: Cataract is the leading cause of avoidable blindness in most parts of developing world, including India. The objectives were to assess cataract surgical coverage (CSC) and investigate the determinants for CSC among people aged 50 years or older in India.Methods: A population-based, cross-sectional survey was conducted to include 2023 residents aged ≥50 years old from 72 clusters of 20 districts in six states from various parts of India. Presenting visual acuity (VA), history of cataract surgery and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 17 publications
3
8
3
1
Order By: Relevance
“…Similar to this study Bharath et al also reported significantly increased the prevalence of CS with increased age, however, it showed a non-significant association of CSC with sex. [13] Unlike current study, Nirmalan et al reported inverse association of CSC with illiteracy and with female sex in rural areas. [11] The reason might be due to people have to reach out far to avail medical services in the rural areas.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Similar to this study Bharath et al also reported significantly increased the prevalence of CS with increased age, however, it showed a non-significant association of CSC with sex. [13] Unlike current study, Nirmalan et al reported inverse association of CSC with illiteracy and with female sex in rural areas. [11] The reason might be due to people have to reach out far to avail medical services in the rural areas.…”
Section: Discussioncontrasting
confidence: 82%
“…[12] Bharath et al report the CSC estimates (persons) at the same VA cutoffs as 75.0% and 91.6%. [13] Murthy et al conducted RAAB survey during 2006-2007 in 16 districts in India reported the CSC for persons as 66.0% and 82.3% at a VA cutoffs of <6/60 and <3/60, respectively. [14] The lesser coverage in our study compared to other studies may be due to our inclusion criteria of functional disability rather than visual acuity for operable cataract, resulted in higher number of cases with operable cataract.…”
Section: Discussionmentioning
confidence: 99%
“…The cataract surgery rate and coverage in India have both increased, as has been seen in various comparative studies. 11 Nevertheless, with the increasing number of elderly, the backlog of cataract related visual impairment in India has not yet been eliminated. Health education methods and strategies will only be effective if they are able to curb the barriers that prevent these patients from seeking timely treatment services.…”
Section: Resultsmentioning
confidence: 99%
“…7 The regional difference of cataract surgical coverage rate had affected to the prevalence of blindness due to cataract in India. 8 India is committed to reduce burden of preventable blindness by the year 2020 by adapting strategies advocated by Vision 2020. It's a collaborative effort of different sectors and organizations towards national plan of action to achieve goals of "right to sight".…”
Section: Introductionmentioning
confidence: 99%